Spinal Anesthesia and Minimal Invasive Laminotomy for Paddle Electrode Placement in Spinal Cord Stimulation: Technical Report and Clinical Results at Long-Term Followup. (1st April 2012) - Sarubbo, S.; Latini, F.; Tugnoli, V.; Quatrale, R.; Granieri, E.; Cavallo, M. A.
Abstract : Object . We arranged a mini-invasive surgical approach for implantation of paddle electrodes for SCS under spinal anesthesia obtaining the best paddle electrode placement and minimizing patients' discomfort. We describe our technique supported by neurophysiological intraoperative monitoring and clinical results. Methods . 16 patients, affected by neuropathic pain underwent the implantation of paddle electrodes for spinal cord stimulation in lateral decubitus under spinal anesthesia. The paddle was introduced after flavectomy and each patient confirmed the correct distribution of paresthesias induced by intraoperative test stimulation. VAS and patients' satisfaction rate were recorded during the followup and compared to preoperative values. Results . No patients reported discomfort during the procedure. In all cases, paresthesias coverage of the total painful region was achieved, allowing the best final electrode positioning. At the last followup (mean 36.7 months), 87.5% of the implanted patients had a good rate of satisfaction with a mean VAS score improvement of 70.5%. Conclusions . Spinal cord stimulation under spinal anesthesia allows an optimal positioning of the paddle electrodes without any discomfort for patients or neurosurgeons. The best intraoperative positioning allows a better postoperative control of pain, avoiding the risk of blind placements of the paddle or further surgery for their replacement.